2017
DOI: 10.18203/2394-6040.ijcmph20173653
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness study of antidiabetic drugs in type 2 diabetes mellitus patients from Mumbai, India

Abstract: Background: Diabetes is fast gaining the status of a potential epidemic in India, with >62 million individuals currently diagnosed with the disease. India currently faces an uncertain future in relation to the potential burden that diabetes may impose on the country. An estimated US$ 2.2 billion would be needed to sufficiently treat all cases of type 2 diabetes mellitus (T2DM) in India. Many interventions can reduce the burden of this disease. However, health care resources are limited; thus, interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…Diabetes, a chronic disease, needs lifelong therapy and hence the cost becomes an important factor in choosing the antidiabetic medication. Other studies by Tandon et al, [22] George et al, [23] and Limaye et al [24] found similar observations.…”
Section: Discussionsupporting
confidence: 68%
“…Diabetes, a chronic disease, needs lifelong therapy and hence the cost becomes an important factor in choosing the antidiabetic medication. Other studies by Tandon et al, [22] George et al, [23] and Limaye et al [24] found similar observations.…”
Section: Discussionsupporting
confidence: 68%
“…In general, insulin, SGLT2i, DPP4i and GLP-1RA medications are more costly than the relatively inexpensive metformin and sulfonylureas [20]. Glimepiride and gliclazide daily treatment costs are 7 and 8 Indian rupees (Rp), respectively, compared with 44 Rp for the DPP4i vildagliptin [76]. Also of note, in India, approximately 80% of people pay 'out of pocket' for their type 2 diabetes management, posing a significant economic burden.…”
Section: Affordability and Accessibility Of Type 2 Diabetes Treatmentmentioning
confidence: 99%
“…1 kasus (2%). Kombinasi metformin dan glimepiride lebih efektif daripada monoterapi metformin(Limaye et al, 2017). Pengobatan lini pertama untuk DM tipe II adalah monoterapi dengan pengobatan tunggal atau manajemen gaya hidup.…”
unclassified